Kajian Budaya Organisasi dan Pengaruhnya terhadap Perilaku Kerja Pegawai dalam Pelaksanaan Otonomi Daerah di Sekretariat Daerah Kota Kendari - Sahrun . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
The objective of this research are to analyze the organizational culture and employee work behavior in Regional Secretariat of Kendari City and to analyze the influence of organizational culture toward employee performance in Regional Secretariat of Kendari City. The population in this research were all the civil servants in Regional Secretariat of Kendari City amounts 249 people. The sample was taken by random sampling that set of 30% or 88 people, whereas the informant of this research were the regional secretary and head of division. The result of this research showed that organizational culture in Regional Secretariat of Kendari City that was measured by indicator such as organizational direction, integration, leadership support, tolerance to criticism/suggestion and control which has been in the category of good culture/high. Similarly, employee work behavior was measured through indicators: enthusiasm and work fervor, work power initiative, work involvement, and the commitment toward organization already indicated a good work behavior. The organizational culture in Regional Secretariat of Kendari City has positive and significant influence toward employee work behavior, in this case, if Regional Secretariat of Kendari City will increase the employee work behavior, one of the factors that pay attention is increase the organizational culture. In order to increase the organizational culture and work behavior become better, then Regional Secretariat of Kendari City needs to socialize about vision and mission of organization and gives explanation about the organizational goals, creating a working system that can facilitate the implementation of the work, besides that it should open up in terms of receiving suggestions and criticisms submitted by employees. Keywords: organizational culture, work behaviour